2018
DOI: 10.1002/lary.27536
|View full text |Cite
|
Sign up to set email alerts
|

Correlating videofluoroscopic swallow study findings with subjective globus location

Abstract: Objective Patients with globus, the sensation of something stuck in the throat, are evaluated by otolaryngologists, gastroenterologists, and speech pathologists and often undergo multiple tests and interventions. We hypothesize that a videofluoroscopic swallow study (VFSS) is useful to characterize globus etiology and correlate subjective globus location to atypical VFSS findings. Method Retrospective chart review of all patients undergoing VFSS over a 24‐month period with a primary complaint of globus. Globus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Idiopathic globus is diagnosed when the clinical history is supportive and after alternate medical conditions have been excluded using prudent and specific investigation, including laryngoscopic evaluation, endoscopy with biopsy, high‐resolution manometry (HRM), and in some instances, ambulatory reflux monitoring 1 . Although as many as 90% of patients presenting to ENT clinics are reported to have abnormal bolus propulsion on videofluoroscopic examination, these do not necessarily correlate to the location or nature of the symptom 3,11 . Abnormal endoscopy (22%), abnormal pH testing (20%), motor abnormalities on HRM (63%), and abnormal barium swallow (24%) were reported in 172 patients presenting to ENT clinics for evaluation 12 .…”
Section: Etiology Of Globusmentioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic globus is diagnosed when the clinical history is supportive and after alternate medical conditions have been excluded using prudent and specific investigation, including laryngoscopic evaluation, endoscopy with biopsy, high‐resolution manometry (HRM), and in some instances, ambulatory reflux monitoring 1 . Although as many as 90% of patients presenting to ENT clinics are reported to have abnormal bolus propulsion on videofluoroscopic examination, these do not necessarily correlate to the location or nature of the symptom 3,11 . Abnormal endoscopy (22%), abnormal pH testing (20%), motor abnormalities on HRM (63%), and abnormal barium swallow (24%) were reported in 172 patients presenting to ENT clinics for evaluation 12 .…”
Section: Etiology Of Globusmentioning
confidence: 99%
“…While globus is common, prevalence varies widely depending on the definition utilized. In one study, only 51% of 216 patients localized globus to the high neck; of the remainder, 35% localized the symptom between the thyroid notch and sternum, and 15% substernally 3 . Prevalence rates as low as 0.1% and as high as 46% have been reported, with females presenting for evaluation more often than males 4‐6 .…”
Section: Introductionmentioning
confidence: 99%
“…Early fluoroscopic studies suggested symptoms above the sternal notch represented pharyngeal dysfunction with decent accuracy, but more recent fluoroscopic and manometric data indicate frequent discordance between symptom localization and abnormal objective findings. [32][33][34][35][36][37] A 2018 study investigating patients with pharyngeal swallowing symptoms that were found to have a structural cause identified structural abnormality in the pharynx in only 41%. 37 Nineteen out of 48 (39%) esophageal cancers found in this study presented with pharyngeal symptoms alone.…”
Section: The Oropharyngeal Assessmentmentioning
confidence: 99%